Low-Load Resistance Training With Blood Flow Restriction Improves Clinical Outcomes in Musculoskeletal Rehabilitation: A Single-Blind Randomized Controlled Trial - Ladlow, Peter; Coppack, Russell J.; Dharm-Datta, Shreshth; Conway, Dean; Sellon, Edward; Patterson, Stephen D.; Bennett, Alexander N. (Frontiers in Physiology, 2018)
Background: There is growing evidence to support the use of low-load blood flow restriction (LL-BFR) exercise in musculoskeletal rehabilitation. Purpose: The purpose of this study was to evaluate the efficacy and feasibility of low-load blood flow restricted (LL-BFR) training versus conventional high mechanical load resistance training (RT) on the clinical outcomes of patient’s undergoing inpatient multidisciplinary team (MDT) rehabilitation. Study Design: A single-blind randomized controlled study Methods: Twenty-eight lower-limb injured adults completed a 3-week intensive MDT rehabilitation program. Participants were randomly allocated into a conventional resistance training (3-days/week) or twice-daily LL-BFR training group. Outcome measurements were taken at baseline and 3-weeks and included quadriceps and total thigh muscle cross sectional area (CSA) and volume, muscle strength (5 repetition maximum (RM) leg press and knee extension test, isometric hip extension), pain and physical function measures (Y-balance test, multistage locomotion test - MSLT). Results: A two-way repeated measures ANOVA revealed no significant differences between groups for any outcome measure post-intervention (p>0.05). Both groups showed significant improvements in mean scores for muscle CSA/volume, 5-RM leg press, and 5RM knee extension (p<0.01) after treatment. LL-BFR group participants also demonstrated significant improvements in MSLT and Y-balance scores (p<0.01). The Pain scores during training reduced significantly over-time in the LL-BFR group (p=0.024), with no adverse events reported during the study. Conclusion: Comparable improvements in muscle strength and hypertrophy were shown in LL-BFR and conventional training groups following in-patient rehabilitation. The LL-BFR group also achieved significant improvements in functional capacity. LL-BFR training is a rehabilitation tool that has the potential to induce positive adaptations in the absence of high mechanical loads and therefore could be considered a treatment option for patients suffering significant functional deficits for whom conventional loaded RT is contraindicated. Trial Registration: ISRCTN Reference: ISRCTN63585315, dated 25 April 2017